Internacionalização de empresas: um estudo sobre as influências das consultorias de gestão - Pastore, Osmar Rezende de Abreu (2015)
This research aimed to construct a theoretical model for the company s internationalization with the intervention of organizing consultants. It was conducted through a qualitative research with unstructured interviews applied to nine business leaders who internationalized their companies using the consultant s support. It was found that the consulting firms, for the companies included in this study, had strong decision power on the alternatives adopted by its customers, enabling a new insight into the conditions of internationalization processes, studied mostly under the light of the firm s structural characteristics and their market forces. This study should be relevant to explain the participation of consulting companies in a framework that supports the study of business internationalization phenomenon with potential contributions, both in the theoretical and practical field. For scholars and teachers can contribute to a better understanding of business internationalization process, incorporating new factors considered in the characterization of this process. For researchers can help in creating larger models representing the business internationalization phenomenon, increasing the level of explanation of the phenomenon by introducing variables directly related to consulting activity. In addition, for business owners and general managers may indicate the need to create strategies to monitor interests and incorporate alignment elements of the consulting activities within international projects - or other types of projects that resemble them - in order to increase the adherence of alternatives offered to the interests of their own organizations.